2001
DOI: 10.1074/jbc.m107692200
|View full text |Cite
|
Sign up to set email alerts
|

Nestin Is a Neuroepithelial Target Gene of Thyroid Transcription Factor-1, a Homeoprotein Required for Forebrain Organogenesis

Abstract: Thyroid transcription factor-1 (TTF-1, also known as NKX2.1 and T/EBP), a transcription factor belonging to the NKX-2 family of homeodomain-containing genes, plays an essential role in the organogenesis of the thyroid gland, lung, and ventral forebrain. Nestin is an intermediate filament protein strongly expressed in multipotential neuroepithelial stem cells and rapidly down-regulated during postnatal life. Here we show that stable fibroblastic clones expressing TTF-1 acquire a phenotype reminiscent of neuroep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 41 publications
1
29
0
Order By: Relevance
“…gene through direct DNA binding to a NestBS site similar to HRE/CRE, bearing a 5'-TGAGGTCA-3' core sequence (Lonigro et al, 2001). We then compared the basal transcriptional activity of this enhancer in two different cell lines of neural (Neuro2A) or non-neural (NIH3T3) origin by transfection of the previously described luciferase reporter construct pNes-Luc, bearing the CNS-specific enhancer (Lonigro et al, 2001).…”
Section: B C Amentioning
confidence: 99%
See 1 more Smart Citation
“…gene through direct DNA binding to a NestBS site similar to HRE/CRE, bearing a 5'-TGAGGTCA-3' core sequence (Lonigro et al, 2001). We then compared the basal transcriptional activity of this enhancer in two different cell lines of neural (Neuro2A) or non-neural (NIH3T3) origin by transfection of the previously described luciferase reporter construct pNes-Luc, bearing the CNS-specific enhancer (Lonigro et al, 2001).…”
Section: B C Amentioning
confidence: 99%
“…mice the organogenesis of the ventral forebrain is profoundly perturbed, elucidating the mechanisms by which TTF-1/NKX2.1 is able to play its fundamental role in the development of the forebrain might be important to achieve a better comprehension of brain organogenesis. In order to better elucidate the function of TTF-1/NKX2.1 in the developing forebrain, we performed an analysis of brain-specific TTF-1/NKX2.1 target genes, and we found that TTF-1/NKX2.1 ectopic expression in fibroblastic cells strongly up-regulates the endogenous transcription of the neuroepithelial cell marker nestin, by direct DNA-binding to an already characterized enhancer capable of recapitulate the CNS-specific expression of the nestin gene in transgenic mice (Lonigro et al, 2001;Zimmerman et al, 1994). TTF-1/NKX2.1 bound to the CNS-specific enhancer through a NestBS site, already known by transgenic mice analysis to be essential for proper nestin expression in the telencephalic portions of the forebrain from 12.5 d.p.c onwards (Josephson et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The antibody recognized an intermediate filament protein whose precise expression pattern is regulated by a conserved enhancer that directs gene expression to neural precursors (Lendahl et al 1990;Zimmerman et al 1994). These powerful regulatory elements in the nestin gene are now widely used to achieve specific genetic manipulation of the brain (Josephson et al 1998;Lonigro et al 2001;Tanaka et al 2004). The initial identification of precursor cells in vivo was followed by evidence that proliferating nestin-positive cells would generate functional neurons in vitro and that these cells would incorporate into the brain (Cattaneo and McKay 1990;Renfranz et al 1991;Vicario-Abejón et al 1995.…”
mentioning
confidence: 99%
“…Questions remain, however, as to how the nestin gene establishes its tissue specific expression in neural stem cells in vivo. A reasonable speculation is that the specific CNS expression may be mediated by the tissue-specific enhancer in the second intron of the nestin gene [14,[16][17][18]. Similar to the nestin gene promoter, many intermediate filament gene promoters are also regulated by Sp1 and Sp3 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The neural stem cell-specific enhancer resides in the 3 0 -region of the second intron [16,17], and a cis-element for the POU transcription factors is responsible for nestin expression in the CNS [17]. It has been shown that nestin is a target gene of thyroid transcription factor-1 (TTF-1, also known as Nkx2.1), which is involved in the organogenesis of the forebrain [18]. However, the structure and function of the nestin gene promoter remained unclear.…”
Section: Introductionmentioning
confidence: 99%